2016
DOI: 10.1007/s11262-016-1420-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HCV genotypes in Yunnan Province of Southwest China

Abstract: Recently, we reported that the frequency of hepatitis C virus (HCV) genotypes and subtypes has rapidly changed among intravenous drug users (IDUs) in Yunnan Province over the last 5 years; this is especially true for subtype 6a which has increased in frequency from 5 to 15%. Here, we assessed 120 HCV-positive plasma samples from the general population (GP). HCV NS5B fragments were amplified and sequenced by PCR. We identified four HCV genotypes (1, 2, 3 and 6) and seven HCV subtypes (1b, 2a, 3a, 3b, 6a, 6n, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Previous studies have shown that genotypes 3 and 6 are mainly prevalent in IDUs . However, through stratification analysis by risk groups, we observed that these subtypes were already highly prevalent in the population of volunteer blood donors and individuals with recent unprotected sexual encounters, consistent with former findings that the HCV subtypes in IDUs are spreading to the general population by sharing infected equipment and through high‐risk sexual behaviors .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that genotypes 3 and 6 are mainly prevalent in IDUs . However, through stratification analysis by risk groups, we observed that these subtypes were already highly prevalent in the population of volunteer blood donors and individuals with recent unprotected sexual encounters, consistent with former findings that the HCV subtypes in IDUs are spreading to the general population by sharing infected equipment and through high‐risk sexual behaviors .…”
Section: Discussionsupporting
confidence: 90%
“…The subtypes were determined by phylogenic comparison to reference sequences for HCVs, by using MEGA 4.0. 14 …”
Section: Methodsmentioning
confidence: 99%
“…This might happen through transfusion of blood and blood products, surgery, organ transplantation, intravenous drug use, tattooing, hemodialysis, unsafe injection practices, mother to fetus, and sexual intercourse[ 5 - 8 ]. However, sexual transmission of HCV is less common and most often observed among men who have sex with men and HIV-infected patients[ 9 , 10 ].…”
Section: Hcvmentioning
confidence: 99%